Calculation of Smith's Mean Measure of Divergence for Intergroup Comparisons Using Nonmetric Data - Edward F. Harris; Torstein Sjøvold (Dental Anthropology Association, 2004)
The Mean Measure of Divergence (MMD) is a formula that converts a battery of trait frequencies into a numerical value such that the more dissimilar two samples are, the greater the value. This measure of phenetic distance was developed by the statistician Cedric A. B. Smith and has become popular among dental anthropologists and osteologists for estimating the dissimilarity among groups in order to help reconstruct populations' movements and structure over time and space. The purpose of the present study is to present the correct formulae and procedures for the MMD given that (1) numerous errors have entered into the literature concerning the formulae themselves, (2) improvements have been described that should be incorporated, and (3) various misunderstandings and misinterpretations have developed that need clarification.